Does the colour of the mug influence the taste of the coffee? - Spence, C; Van Doorn, G; Wuillemin, D (BioMed Central, 2014)
Background We investigated whether consumers’ perception of a café latte beverage would be influenced by the colour (transparent, white or blue) of the mug from which it was drunk. Results In experiment 1, the white mug enhanced the rated “intensity” of the coffee flavour relative to the transparent mug. However, given slight physical differences in the mugs used, a second experiment was conducted using identical glass mugs with coloured sleeves. Once again, the colour of the mug was shown to influence participants’ rating of the coffee. In particular, the coffee was rated as less sweet in the white mug as compared to the transparent and blue mugs. Conclusions Both experiments demonstrate that the colour of the mug affects people’s ratings of a hot beverage. Given that ratings associated with the transparent glass mug were not significantly different from those associated with the blue mug in either experiment, an explanation in terms of simultaneous contrast can be ruled out. However, it is possible that colour contrast between the mug and the coffee may have affected the perceived intensity/sweetness of the coffee. That is, the white mug may have influenced the perceived brownness of the coffee and this, in turn, may have influenced the perceived intensity (and sweetness) of the coffee. These results support the view that the colour of the mug should be considered by those serving coffee as it can influence the consumer’s multisensory coffee drinking experience. These results add to a large and growing body of research highlighting the influence of product-extrinsic colour on the multisensory perception of food and drink.